Labor Market Competition and Attitudes toward Immigrants: New Evidence from Asia - Zeewan Lee; Joelle H. Fong (ZBW - Leibniz Information Centre for Economics, 2023)
Immigrants in a destination country both alter the prospects of economic development and influence the livelihood of natives. Using data from 10 Asian countries in the 2018-2020 World Value Survey (WVS), we provide new evidence regarding the impact of skill-driven labor market competition on natives' attitudes toward immigrants. Linking information on occupation-specific human capital accumulation from O*NET to WVS, we explore granular dimensions of natives' skills and their implications for labor market competition and vulnerability. To account for the possibility of reverse causality (selection in natives' occupational choices resulting from natives' inherent preferences toward immigrants), we run the two-stage instrumental variable estimator adopting the control function approach. Holding educational levels constant, we find that natives with greater manual skills and fewer communication skills are more likely to be pro-immigration. We also find that the links between manual skills and attitudes are driven primarily by the level of flexibility in natives' skills, while the negative impacts of communication skills are driven by natives' writing abilities. Our results offer important insights for policymakers in Asia to establish nuanced immigration policies and skill-development programs that account for their impacts on intergroup labor market competition and social cohesion.
Keywords: F66; F68; J61; J68; 330; attitudes; immigration; labor market competition; skills; human capital accumulation; control function approach